The association between sugar-sweetened beverages and milk intake with emotional and behavioral problems in children with autism spectrum disorder - Tan, Si; Pan, Ning; Xu, Xiaoyu; Li, Hailin; Lin, Lizi; Chen, Jiajie; Jin, Chengkai; Pan, Shuolin; Jing, Jin; Li, Xiuhong (Frontiers in Nutrition, 2022)
Background: Emotional and behavioral problems are common in children with autism spectrum disorder (ASD). It’s still unclear whether children with ASD have abnormal sugar-sweetened beverages (SSBs) and milk intake and whether this abnormality will affect their emotion and behavior remains unclear. The current study aims to investigate the association of SSBs and milk intake with emotional and behavioral problems in children with autism spectrum disorder (ASD). Methods: 107 children with ASD and 207 typical developing (TD) children aged 6-12 years old were recruited in the study. The frequency of SSBs and milk intake was assessed by self-designed questionnaire. Emotional and behavioral problems were assessed by Strength and Difficulties Questionnaire (SDQ). Then, the generalized linear model was produced to evaluate the association of SSBs and milk intake with emotional and behavioral problems. Results: In the current study, there was no difference in frequency of SSBs intake between children with ASD and TD children (p > 0.05), and children with ASD consumed more milk compared to TD children (p < 0.05). After adjusting sex, age, maternal and paternal education, monthly family income, we found significant difference in each subscale scores of SDQ in two groups (p < 0.05). In children with ASD, higher frequent SSBs intake was positively associated with the scores of the emotional problem (p for trend < 0.05), and lower frequent milk intake was inversely associated with the scores of the prosocial behavior (p for trend < 0.05). No interactive effects were found on SSBs and milk intake with emotional and behavioral problems (p for trend > 0.05). Conclusion: In children with ASD, frequency of SSBs and milk intake was associated with emotional problem and prosocial behavior, respectively. Children with ASD should increase the frequency of milk intake and decrease the frequency of SSBs intake.